98.0k views
4 votes
Please help me. I dont understand.

Please help me. I dont understand.-example-1

2 Answers

3 votes


\bf -3(1)/(8)+\left( -2(1)/(2) \right)\implies -3(1)/(8)+1* \left( -2(1)/(2) \right)\implies -3(1)/(8)-2(1)/(2)

User Madebydavid
by
5.8k points
5 votes

subtracting a number is the same as adding the opposite of the number

for example:

7 - 6 = 1

7 + (-6) = 1

since you are subtracting 2
(1)/(2), it is the same as adding -2
(1)/(2)

so your answer should be

A) -3
(1)/(8) + (-2
(1)/(2) )

hope this helped!

User Manish Sinha
by
5.5k points